Effects of the post-modification using bismuth chelate (BisBAL) on the anti-biofouling and performance properties of flat-sheet microfiltration membranes. (June 2018) - Kose-Mutlu, Borte; Turken, Turker; Guclu, Mehmet C.; Guclu, Serkan; Ovez, Suleyman; Koyuncu, Ismail
Highlights: MF membranes were modified by adsorption BisBAL. Dip coating, spin coating, and low pressure-treated coating were studied. Modified membranes has strong resistance to biofouling. Abstract: Membrane biofouling defined as the attachment and growth of microorganisms on a membrane surface has been a major problem of membrane bioreactor (MBR) technology. The anti-biofouling properties like the inhibition of bacterial adhesion of a membrane are quite significant for a long-term MBR operation. Surface modification is thought to be one of the most common approaches to improve this property. In this study, polymeric microfiltration membranes were modified by adsorption BisBAL, which is a synthesized chelate using bismuth and have a high anti-bacterial effect on various microorganisms, on the membrane surface using dip coating (DC), spin coating (SC), and low pressure-treated coating (LPtC). The purpose was to increase the surface hydrophilicity, change the surface charge, and gain the surface an anti-bacterial characteristic. It was found that the higher adsorption time, lower feed flow rate and higher spinning velocity, and pressure application increased the efficiency of the process during DC, SC, and LPtC, respectively. Furthermore, improved strategies allow the adsorption of BisBAL on the membrane surface and modified membranes has strong resistance to biofouling. Since modification resulted in a decrease in pore fouling and irreversible fouling for all type of membranes, these membranes can be novel alternatives for energy-saving MBR operation.